Persepsi pekerja terhadap pusing ganti kerja kajian kes di Hotel Grand Continental - Lim, Chiew Thing (Universiti Malaysia Sarawak (UNIMAS), 1999)
This study aims to determine the perception of the employees toward the job turnover in Grand Continental Hotel, Kuching, and the factors that influence their perception. The factors include demographic characteristics such as age, educational level and working period, wages, promotion opportunity, working environment, relationship with the management and relationship with the co-workers. Some concepts selected from the previous studies are revealed to further enhance the understanding of the readers. In this study, the questionnaire method is used to obtain feedback and the relevant data. A total of 75 employees from 9 departments were randomly chosen as the sample of the study. The respondents' background, their perception towards turnover and the respondents'opinion towards the related factors were examined. The data of the study was analyzed using the descriptive and inferential statistics. A majority (85.3 percent) of the respondents have moderate perception toward the turnover, 4 percent have low perception and 10.7 percent have high perception. Most of the respondents also have moderate perception towards the factors that have been mentioned. The Correlation Pearson test, ANOV A and Multiple Linear Regression were used to test the hypotheses. The result shows that the correlation between wages, promotion opportunity, working environment and relationship with the management with perception are found to be positive and significant, whereas there is no correlation in the relationship with the co-workers. There is no significant difference between age, educational level and working period with the perception towards turnover. In terms of the working environment, promotion opportunity and relationship with the management, the correlation is found to be moderate. In terms of wages, it shows a weak correlation with turnover. It is found that the working environment is the dominant factor, followed by relationship with the management, promotion opportunity and wages that contribute to the perception of turnover. These findings show that the related factors should be given serious attention to retain employees in the organization. Some suggestions have been recommended for the organization and for future research to be more complete.